Temporary Renal Enlargement in Children with a First Episode of Febrile Urinary Tract Infection is a Significant Risk of Recurrent Infection - Ishimori, Shingo; Fujimura, Junya; Oyama, Shohei; Shinomoto, Tadashi; Onishi, Satoshi; Hattori, Kengo; Okizuka, Yo; Nishiyama, Atsushi; Minami, Hirotaka (Urology Journal, 2022)
Purpose: Although morphological renal abnormalities in children with febrile urinary tract infection (fUTI) have been showed a predictive factor for recurrent infection, there are no available data on recurrence regarding sonographic renal enlargement at first fUTI episode, especially focusing on whether renal enlargement is temporary or not. Materials and Methods: This cohort study reviewed the medical records of children who underwent renal ultrasound during their first fUTI during 2005–2013 and who were aged <15 years at diagnosis. We defined a kidney as temporary enlarged when the kidney length was ≥2 standard deviation above normal renal length for that age on sonography or a difference of ≥1 cm in sonographic length between the right and left kidneys, following normal renal length after antibiotic treatment. Results: A total of 132 children were enrolled, of whom 11 had sonographic temporary temporal renal enlargement during their first fUTI. After completing antibiotic therapy for a first fUTI episode, 20 (15%) children had fUTI recurrence. The clinical characteristics at first episode of fUTI were not significantly different between renal enlargement and nonrenal enlargement groups. Children with temporary renal enlargement at a first fUTI episode had significantly lower fUTI recurrence-free survival proportion than those with nonrenal enlargement according to the Kaplan–Meier method (p = 0.003) Conclusion: Identification of temporary temporal renal enlargement as a predictor of recurrent fUTI may help identify children with a first episode of fUTI who will be warned of close monitoring.